Overexpression of NT-3 in the hippocampus suppresses the early phase of the adult neurogenic process - Kasakura, Nanami; Murata, Yuka; Shindo, Asuka; Kitaoka, Shiho; Furuyashiki, Tomoyuki; Suzuki, Kanzo; Segi-Nishida, Eri (Frontiers in Neuroscience, 2023)
The dentate gyrus (DG) of the hippocampus regulates stress-related emotional behaviors and ensures neurogenesis throughout life. Neurotrophin-3 (NT-3) is a neurotrophic factor that regulates neuronal differentiation, survival, and synaptic formation in both the peripheral and central nervous systems. NT-3 is expressed in the adult DG of the hippocampus; several chronic stress conditions enhance NT-3 expression in rodents. However, functional modulation of the adult DG by NT-3 signaling remains unclear. To directly investigate the impact of NT-3 on DG function, NT-3 was overexpressed in the hippocampal ventral DG by an adeno-associated virus carrying NT-3 (AAV-NT-3). Four weeks following the AAV-NT-3 injection, high NT-3 expression was observed in the ventral DG. We examined the influence of NT-3 overexpression on the neuronal responses and neurogenic processes in the ventral DG.NT-3 overexpression significantly increased the expression of the mature DG neuronal marker calbindin and immediate early genes, such as Fos and Fosb, thereby suggesting DG neuronal activation. During neurogenesis, the number of proliferating cells and immature neurons in the subgranular zone of the DG significantly decreased in the AAV-NT-3 group. Among the neurogenesis-related factors, Vegfd, Lgr6, Bmp7, and Drd1 expression significantly decreased. These results demonstrated that high NT-3 levels in the hippocampus regulate the activation of mature DG neurons and suppress the early phase of neurogenic processes, suggesting a possible role of NT-3 in the regulation of adult hippocampal function under stress conditions.